3=g+1

Simple and best practice solution for 3=g+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3=g+1 equation:


Simplifying
3 = g + 1

Reorder the terms:
3 = 1 + g

Solving
3 = 1 + g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-1g' to each side of the equation.
3 + -1g = 1 + g + -1g

Combine like terms: g + -1g = 0
3 + -1g = 1 + 0
3 + -1g = 1

Add '-3' to each side of the equation.
3 + -3 + -1g = 1 + -3

Combine like terms: 3 + -3 = 0
0 + -1g = 1 + -3
-1g = 1 + -3

Combine like terms: 1 + -3 = -2
-1g = -2

Divide each side by '-1'.
g = 2

Simplifying
g = 2

See similar equations:

| 2/7x=3 | | 7=9y-2 | | 1/3y=1/5 | | 2w+46=10w+74 | | 4x-4y+112=180 | | (7y+4)-(3+6y)=10 | | 4x^2-8xy-3x+6= | | 7y-37=8y-46 | | 5x+4=2(x+5) | | 5p+9=18+4p | | -2/7v=16 | | y-3=-7x | | (2x-5)*(2x-5)=121 | | 8t-46=7y-37 | | 3/2k=18 | | X+5+4x-15=90 | | -3/-3/7 | | 1.11-2.2t=3.9 | | 4x-1=3x+4x-4 | | 6.67-6.4x+1.11=22.5 | | v-23=2v-87 | | 7v/8-8v-4/5v-2 | | 72/-12 | | 8x+12y=8 | | 7(5z+-5)= | | s=2s-61 | | 1/3c=32 | | 2s-61=s | | 4x^2-44x+96=0 | | 0.4(x-4)=0.8 | | -0.12=y/-0.5 | | -7(1+3r)= |

Equations solver categories